Desenvolvimento de uma família de reatores eletrônicos para lâmpadas de multivapor metálico empregando a técnica de conexão diferencial de conversores CC/CC - Cervi, Murilo (2009)
This work presents and analyzes a new family of electronic ballasts to supply metal halide lamps applied to interior lighting systems. These lamps present the best light quality among the high intensity discharge lamps, and its compactness results a good choice for interior lighting systems application. The electrical characteristics of the high intensity discharge lamps are evaluated, and it is presented an alternative for supplying these lamps in a safe and reliable way. This alternative consists of using high frequency DC/DC converters in order to supply the lamp with a low frequency, symmetrical square waveform. A family of electronic ballasts is presented, which all the topologies are obtained from the differential connection of DC/DC converters. The analysis of these proposed and designed systems brings the main advantages and disadvantages of using each topology, related both to the components design and to the restrictions implied by each topology.